Should patients receive consolidation chemotherapy before reduced intensity allogeneic hematopoietic stem cell transplantation for acute myeloid leukemia in first complete remission? - Byun, Ja Min (Ther Adv Hematol, 2021)
BACKGROUND: For acute myeloid leukemia (AML) patients, the role of bridging consolidation chemotherapy after achieving first complete remission (CR1) in the transplant setting is a frequently debated issue. The lack of data from Asian patients led us to conduct this study. METHODS: We retrospectively studied outcomes of 106 patients in CR1 undergoing allogeneic stem cell transplantation (alloSCT) with reduced intensity conditioning (RIC) based on their exposure to pre-transplant consolidation chemotherapy. There were 35 in the no consolidation group versus 71 in the consolidation group. RESULTS: The median relapse free survival (RFS) was 9 months for the no consolidation group and 51 months for consolidation group (p = 0.023). The median overall survival was 32 months for the no consolidation group and not reached for the consolidation group (p = 0.034). Multivariate analysis recognized consolidation and poor cytogenetics as adverse prognostic factors for RFS. Moreover, RFS was better in patients with a shorter time lapse between last chemotherapy and alloSCT in both the no consolidation group and the consolidation group. Consolidation chemotherapy did not negatively affect neutrophil and platelet engraftment, infection rates, or acute graft-versus-host disease (GVHD) incidence. On the other hand, patients undergoing consolidation chemotherapy showed trends towards a more severe degree of chronic GVHD. CONCLUSION: The exposure to consolidation chemotherapy in CR1 prior to alloSCT with RIC conditioning did not negatively impact the outcomes in Korean AML patients, for whom a suitable donor is rarely immediately available. Therefore, post-remission consolidation chemotherapy is a reasonable option if required.